DNMT1 Level as Biomarker for Early Detection of Nasopharyngeal Carcinoma - Raudah Putri Syari; Zulham Yamamoto; Farhat; Sry Suryani Widjaja; Ririe Fachrina Malisie (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Introduction: Nasopharyngeal carcinoma (NPC) is a malignant disease often diagnosed at an advanced stage. Early detection of NPC is necessary to reduce morbidity and mortality of this disease. To date, early detection methods for NPC still have limitations, especially in terms of positive predictive value. Identification of DNA methylation abnormalities has been studied for its role as a marker for early detection of NPC. Objective: This review describes the potential of DNMT1, an enzyme involved in DNA methylation, as a biomarker for early detection of NPC. Methods: We conducted a literature search using PubMed and Google Scholar databases. The keywords used were "nasopharyngeal carcinoma AND DNMT1", nasopharyngeal carcinoma AND early detection, "nasopharyngeal carcinoma AND screening", nasopharyngeal carcinoma OR DNMT1, “DNMT1 OR Carcinoma”, nasopharyngeal carcinoma OR screening, and nasopharyngeal carcinoma OR early detection. Results: Increased DNMT1 expression is associated with global hypermethylation which is part of the early pathogenesis of NPC. LMP1, as an oncoprotein released by EBV, increases DNMT1 expression and activity. Conclusion: High DNMT1 expression in NPC indicates its potential as an early detection method for NPC.